On the Usefulness of Financial Statement Information: A Suggested Research Approach. - Pankoff, Lyn D.; Virgil, Robert L. (The Accounting Review, 1970)
Abstract The article discusses the information content of financial statements that firms periodically release to the public. It tends to answer what kinds of information would a publicly owned firm disclose about its operations. Increasingly within about the past decade, accountants have come to believe that an important part of the answer to this question lies with the user of financial statements. It lies in knowing what kinds of information about firms are most useful to him. The recognition of the user's importance in the definition of usefulness has led to a number of important empirical measurements of usefulness. Specifically, the article wants to discover the relative value to a prominent user, the investor, of the various kinds of routinely calculated financial statement numbers, such as sales and net income, relative to each other and to some other kinds of quantitative information. It discusses these calculations, with the timeliness of reports or the appropriate media for transmission.